Prevalence of hybrid TLR4+M2 monocytes/macrophages in peripheral blood and lung of systemic sclerosis patients with interstitial lung disease - Gotelli, Emanuele; Soldano, Stefano; Feghali-Bostwick, Carol; Montagna, Paola; Campitiello, Rosanna; Contini, Paola; Mora, Marco; Benelli, Roberto; Hysa, Elvis; Paolino, Sabrina; Pizzorni, Carmen; Sulli, Alberto; et al. (Frontiers in Immunology, 2024)
IntroductionSystemic sclerosis (SSc) is a complex autoimmune connective tissue disease characterized by microvascular damage, immune system reactivity and progressive fibrosis of skin and internal organs. Interstitial lung disease is the leading cause of death for SSc patients (SSc-ILD), and the process of lung fibrosis involves also circulating monocytes and alveolar macrophages.MethodsCurrent study aimed to identify monocyte/macrophage phenotypes in lung and peripheral blood of SSc-ILD patients by immunostaining and flow cytometry, respectively. Single immunostaining was performed using primary antibodies against CD68 (pan-macrophage marker), CD80, CD86, TLR4 (M1 markers), CD163, CD204, and CD206 (M2 markers). Flow cytometry analysis included the evaluation of CD45, CD14, CD16 (monocyte lineage), CD1c (dendritic lineage), together with M1 and M2 activation markers on circulating monocytes. Protein synthesis of TLR4 and M2 markers was also investigated in cultured monocytes-derived macrophages (MDMs) from SSc-ILD patients by Western Blotting.ResultsLung samples were obtained from 9 SSc-ILD patients (50 ± 9 years old) and 5 control non-SSc patients without lung fibrosis (58 ± 23 years old). Alveolar macrophages (CD68+ cells) showed a significantly higher positivity of M1 and M2 markers in SSc-ILD lung samples than in controls (p<0.05 for CD80, p<0.01 for CD86, p<0.001 for CD68, p<0.0001 for TLR4, CD163, CD204 and CD206). In CD68 positive areas of SSc-ILD samples, a significantly higher percentage of TLR4, CD163, CD204, and CD206 positive cells was observed compared to CD80 and CD86 positive cells (p<0.001 in both cases), suggesting the possible presence of hybrid TLR4+M2 macrophages (CD68+CD80-CD86-TLR4+CD163+CD204+CD206+cells) in SSc-ILD samples. A second cohort of 26 SSc-ILD patients (63 ± 14 years old) and 14 SSc patients without ILD (63 ± 19 years old) was recruited for flow cytometry analysis of circulating monocytes. Again, a significantly higher percentage of hybrid TLR4+M2 monocytes (CD1c-CD80-TLR4+CD163+CD204+CD206+cells) was found in SSc-ILD positive than SSc-ILD negative patients (p<0.05). Moreover, the protein synthesis of TLR4 and M2 markers was also found higher in cultured MDMs obtained from SSc-ILD patients than in MDMs from SSc patients without ILD and this increase was significantly higher for CD163 (p<0.05) and CD206 (p<0.01).ConclusionsThe presence of hybrid TLR4+M2 markers on both circulating monocytes and resident lung macrophages in SSc-ILD patients, is reported for the first time. Therefore, the detection of circulating hybrid TLR4+M2 monocytes in SSc-ILD might represent a further potential biomarker of progressive organ fibrosis, to be searched in blood samples of SSc patients.